Concurrent Overexpression of Two Hyaluronidases, KIAA1199 and TMEM2, Strongly Predicts Shorter Survival After Resection in Pancreatic Ductal Adenocarcinoma. Issue 7 (August 2022) - Kudo, Yuzan; Sato, Norihiro; Oba, Takuya; Adachi, Yasuhiro; Amaike, Takao; Koga, Atsuhiro; Kohi, Shiro; Noguchi, Hirotsugu; Nakayama, Toshiyuki; Hirata, Keiji
Abstract : Objectives: Pancreatic ductal adenocarcinoma (PDAC) is characterized by accelerated hyaluronan metabolism. Our previous studies have shown increased expression of 2 newly identified hyaluronidases, KIAA1199 and transmembrane protein 2 (TMEM2), in PDAC. However, the relationship between these 2 hyaluronidases is unknown. In the present study, we investigated the correlation between KIAA1199 and TMEM2 expression in PDAC. Methods: Using quantitative real-time reverse transcription polymerase chain reaction, we analyzed KIAA1199 and TMEM2 mRNA expression in 11 PDAC cell lines and frozen tissues from 12 patients with PDAC. We used immunohistochemistry to investigate expression patterns of KIAA1199 and TMEM2 in archival tissues obtained from 92 patients with PDAC who underwent surgical resection. We compared survival between 4 groups according to expression patterns of KIAA1199 and TMEM2. Results: We found a significantly positive correlation between KIAA1199 and TMEM2 mRNA in PDAC cell lines and tissues. Immunohistochemical analysis found that median overall survival was 30.2 months in patients with low expression of KIAA1199 and TMEM2 and 12.5 months in those with high expression of both. Patients with high expression of KIAA1199 and TMEM2 had significantly shorter survival than other patient groups. Conclusions: Concurrent overexpression of these 2 hyaluronidases could be a strong prognostic marker in PDAC.